Emerging Concepts Linking Obesity with the Hallmarks of Cancer. (January 2017) - Donohoe, Claire L.; Lysaght, Joanne; O'Sullivan, Jacintha; Reynolds, John V.
Abstract : There is compelling epidemiological evidence linking obesity to many tumours; however, the molecular mechanisms fuelling this association are not clearly understood. Emerging evidence links changes in the tumour microenvironment with the obese state, and murine and human studies highlight the relevance of adipose stromal cells (ASCs), including immune cells, both at remote fat depots, such as the omentum, as well as in peritumoural tissue. These obesity-associated changes have been implicated in several hallmarks of cancer, including the chronic inflammatory state and associated cell signalling, epithelial-to-mesenchymal transition (EMT), tumour-related fibrosis, angiogenesis, and genomic instability. Here, we present a summary of developments over the past 5 years, with particular focus on the tumour microenvironment in the obese state. Trends: Gene expression differences have been identified between patients who are obese at the time of cancer diagnosis, in breast, prostate, and endometrial cancers. Murine and human studies indicate differences in the abundance of adipose stromal cells (ASCs) and immune cells in the obese state. There exists interplay between ASCs, such as preadipocytes, and immune cell functionality in the tumour microenvironment. These cells are involved in chronic inflammation and signalling, epithelial-to-mesenchymal transition, tumour-related fibrosis, and angiogenesis. ASCs might be influenced by changes in the systemic hormonal status (e.g., increased aromatase activity resulting in enhanced oestrogen production in breast cancer) or leptin. Emerging hallmarks, such as genomic instability and altered cellular energetics, are noted but their interaction within the microenvironment requires further study.